KAJIAN YURIDIS TERHADAP TINDAK PIDANA KORUPSI - M.H, Ismail (LEGALITE, 2017)
Corruption in Indonesia is so severe as social diseases, reinforced by corrupt practices exposed by the media increasing perceptions of corruption are like illness especially at the end of the New Order era even on the current reform order, almost everywhere. Starting from small officials to high officials. The results of the study indicate an important assertion, because the financial loss of the state is one of the essential elements of corruption in addition to unlawful acts. Thus, the criminal act of corruption is not abolished even then the element of state loss is not proven in court because it has been returned by the suspect, seizure of a number of goods. Barriers at investigation level, juridical investigators remain guided by KUHAP and applicable legislation, investigators lack understanding of the meaning of substance in UUPTPK especially in understanding the element "can enrich themselves or others or a corporation. It is suggested that the regulation regarding the minimum restriction of both the penal provisions and the penalties in UUPTPK to be eliminated because with the inclusion of these minimum limits, may open the possibility of imposition of criminal sanctions imprisonment and fine sanctions that do not reflect a sense of justice to punish the perpetrators of corruption. Anti-corruption laws will be more effective if only the maximum limit is imposed.